Family-Based Anxiety Detection In Primigravida Pregnant Women - Aisyah, Risqi Dewi; Prafitri, Lia Dwi; Abbas, Hasriwiani Habo (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Maternal anxiety during pregnancy, particularly among primigravida women, is a prevalent emotional state that can significantly impact both the mother and fetus. This study explores the relationship between family factors—specifically family support, communication, socioeconomic status, satisfaction with family roles, and family decision-making—and anxiety levels in primigravida pregnant women. Utilizing a cross-sectional observational analytical design, the research included 92 primigravida women from Puskesmas Tirto, Kedungwuni I, and Kedungwuni II. Data were collected through validated and reliable questionnaires and analyzed using multiple logistic regression. The findings reveal significant associations between family support (OR=25.427; 95% CI=1.123-9.078; p=0.007), family communication (OR=239.115; 95% CI=9.144-6252.589; p=0.001), and satisfaction with family roles (OR=107.415; 95% CI=4.231-2726.710; p=0.005) with reduced levels of anxiety. These results underscore the importance of involving family members in antenatal care, enhancing communication, and providing psychological support to manage anxiety effectively. The study highlights the need for healthcare providers to integrate family dynamics into prenatal care strategies to improve maternal mental health and overall pregnancy experience.